Public Sector Financial Management Reform: A Case Study of Local Government Agencies in Indonesia - Monir Mir; Wahyu Sutiyono (Australasian Accounting, Business and Finance Journal, 2013)
Indonesia has taken initiatives to reform its public sector financial management. One of the reform agendas was to introduce ‘cash to accrual’ accounting for improved financial reporting. It is expected that improved financial reporting will enhance financial accountabilities of the governmental agencies and will assist both internal and external decision makers whose decisions will be based on the financial reports. However, it has been observed that there is a significant increase in the number of qualified audit reports when these financial reports were audited. This also means that these financial reports are lacking in providing true and fair views on the financial activities of the governmental agencies, thereby not assisting in discharging their accountabilities. This study seeks to answer the question as to why the numbers of qualified audit reports have increased despite the existence of various governmental accounting reform agendas. Based on the in-depth case studies of three Indonesian local governments, it is found that the demand, the supply and the quality assurance of the accounting information outputs in these local governments are not in parity, and this lacking in parties actually has impacted in producing unqualified and usable accounting reports.
Keywords: Public sector reform; New public management; Financial management; Local government; Indonesia